Efektivitas Peran Tenaga Pendamping dalam Meningkatkan Partisipasi Masyarakat di Bank Sampah Kirana Gajah Mada Kota Pekanbaru - Suryani Suryani (Pelantar Press, 2024)
A wate bank is place used to collect waste that has been sorted. The problem of waste management in urban areas requires public awareness to participate. The community of residents can participate in managing waste, especially in their respective environments. The aim of this research is to determine the effectiveness of facilitator in increasing community participation in the Kirana Gajah Mada waste bank Pekanbaru city. This research was conducted using descriptive qualitative methods. The research was carried out at the Kirana Gajah Mada waste bank Pekanbaru city. The results show an increase in community participation after serving as a waste bank facilitator at the Kirana Gajah Mada waste bank Pekanbaru city. The facilitator effective in increasing the number of people participating in becoming waste bank customers, effectively increasing the amount of waste saved by waste bank customers and affective in increasing the public’s desire to continuously participate in becoming waste bank customers.